2018
DOI: 10.1080/09540105.2018.1463972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microencapsulated probiotics and prebiotics on growth performance, antioxidative abilities, immune functions, and caecal microflora in broiler chickens

Abstract: The study was conducted to evaluate the effects of microencapsulated probiotics and prebiotics in broilers. A total of 108 one-day-old male Arbor Acres broilers were randomly divided into 3 groups (CON: basal diet; MEP: basal diet + compound microecologic products; ANT: basal diet + antibiotics), and there were 6 replicates per group and 6 birds per replicate. Compared with CON, diets supplemented with MEP or ANT significantly increased average daily gain and serum immunoglobulin M level at day 21, and serum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 38 publications
4
31
0
3
Order By: Relevance
“…The predominance of the Lactobacillales is important since the order contains a variety of microorganisms with probiotic potential. The results of the present study support those of Wang et al (2018), who reported that the Lactobacillales were the most predominant order in the ileal mucosa samples, whereas the Clostridiales were the most predominant in cecal digesta samples. Lactobacillus aviaries were most prevalent in the supplemented group, accounting for 57.16, 70.52, and 36.10% of intestinal microbiota sequences from the xylanase, probiotic, and co-supplemented groups, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The predominance of the Lactobacillales is important since the order contains a variety of microorganisms with probiotic potential. The results of the present study support those of Wang et al (2018), who reported that the Lactobacillales were the most predominant order in the ileal mucosa samples, whereas the Clostridiales were the most predominant in cecal digesta samples. Lactobacillus aviaries were most prevalent in the supplemented group, accounting for 57.16, 70.52, and 36.10% of intestinal microbiota sequences from the xylanase, probiotic, and co-supplemented groups, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Abdel-Hafeez et al (2017) reported that feed consumption in the prebiotic group was higher than in control group in broilers. However, Baurhoo et al (2009), Eseceli et al (2010 and Wang et al (2018) reported that feed intake was not influenced by dietary supplementations of AGPs and prebiotics in broilers. The results of the present findings regarding weight gain and FCR are in agreement with the findings of Shahir et al (2014) who reported improved weight gain and FCR in broiler birds fed diet containing yeast based prebiotics.…”
Section: Discussionmentioning
confidence: 98%
“…Many beneficial effects of the dietary application of nondigestible carbohydrates (prebiotics) in poultry have been well-documented [1][2][3][4][5][6]. Inulin fermentation products in the gut have anti-inflammatory effects [7].…”
Section: Introductionmentioning
confidence: 99%